2014
DOI: 10.1007/s00198-014-2703-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of teriparatide and ibandronate on spine bone mineral density (BMD) and microarchitecture (TBS) in postmenopausal women with osteoporosis: a 2-year open-label study

Abstract: Results: Baseline characteristics (overall mean ± SD) were similar between groups in terms of age, 67.9± 7.4 years; body mass index, 23.8 ± 3.8 kg/m 2 ; BMD L1-L4, 0.741 ± 0.100 g/cm 2 and TBS, 1.208 ± 0.100. Over 24 months, teriparatide induced a significantly larger increase in LS BMD and TBS than IBN (+7.6% ± 6.3 vs. +2.9% ± 3.3 and +4.3% ± 6.6 vs.+0.3% ± 4.1, respectively; p < 0.0001 for both). LS BMD and TBS were only weakly correlated at baseline (r 2 = 0.04) with no correlation between the changes in BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 46 publications
8
56
1
2
Order By: Relevance
“…The change in TBS also appears to be influenced by the type of therapy for osteoporosis. Previous studies have reported greater improvement in TBS with an anabolic therapy such as teriparatide compared with a bisphosphonate [37,38]. In this study, denosumab was associated with significantly greater improvement in TBS than placebo at each of the annual assessments.…”
Section: Discussionmentioning
confidence: 44%
“…The change in TBS also appears to be influenced by the type of therapy for osteoporosis. Previous studies have reported greater improvement in TBS with an anabolic therapy such as teriparatide compared with a bisphosphonate [37,38]. In this study, denosumab was associated with significantly greater improvement in TBS than placebo at each of the annual assessments.…”
Section: Discussionmentioning
confidence: 44%
“…Thereby, the increased bone density may not translate as effectively into increased bone stability as in situations where both BMD and TBS increase as in the treatment of postmenopausal osteoporosis (40).…”
Section: Discussionmentioning
confidence: 99%
“…Several relatively small studies have examined treatment-induced changes in TBS [49,50,53,[56][57][58][59] (Table 3). Of these, four were studies of osteoporosis treatment in postmenopausal women, one in both men and women with osteoporosis, and two in the management of breast cancer.…”
Section: Is Tbs Responsive To Treatment?mentioning
confidence: 99%